Four dissertations - Price, Richard (Printed for A. Millar and T. Cadell, 1767)
I. On providence. -- II. On prayer. -- III. On the reasons for expecting that virtuous men shall meet after death in a state of happiness. -- IV. On the importance of Christianity, the nature of historical evidence, and miracles.